PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA USAHA KECIL MENENGAH KABUPATEN GARUT - Hari Mulia (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Service quality can make customers feel satisfied and have optimal loyalty, based on research problems and phenomena that occur, the authors are interested in conducting research on service quality and customer loyalty through research with the title. Effect of Service Quality on Customer Loyalty in Small and Medium Enterprises, Garut Regency. The method used is associative. Collecting data using quantitative, namely research that takes a sample from a population and uses a questionnaire as the main data collection tool, while the population taken a sample of 68 people. To determine the effect of service quality on customer loyalty in Small and Medium Enterprises in Garut Regency, a correlation test analysis, determination test, t test and f test were conducted. Based on the results of service quality testing, the effect on customer loyalty is a very strong category, which is equal to 0.959 and the test of determination is very good, namely 91.9% and the remaining 8.1% is influenced by other factors that are not examined such as switching costs and waiting time, while and the t test. significant effect between service quality on customer loyalty, because this t count is greater than t table, namely 374,69.